History : Another look аnd look of the Other (Journal of Philosophy Culture and Political Science, 2019)
In the article the story is seen through the prism of a different viewand the gaze of the Other. Reveals the history of the concept, look,on the other. We give the concept of monumental, antiquarian and critical history of Friedrich Nietzsche. Revealed the classical andpost-classical concepts of the Other, the theory okulotsentrizmaWestern rationalism. Through these theories and concepts of the story is positioned Barrens, a new chronology, the principles of social theorist. Another view of the problem affects the reliable /unreliable in history, the history / literature, external / internal.Looking the Other – a dialogue of the new / traditional chronology,the historian / philosopher, logic / sensing.